2017
DOI: 10.1063/1.4982845
|View full text |Cite
|
Sign up to set email alerts
|

Mixed convection boundary layer flow over a horizontal circular cylinder in a Jeffrey fluid

Abstract: In this paper, a numerical analysis of boundary layer flow and heat transfer in Jeffrey fluid over a moving flat plate with Newtonian Heating have been presented. The governing partial differential equations were reduced to a transformed ordinary differential equation with the help of similarity transformation. Numerical solutions were obtained for these transformed ordinary differential equation by using the Runge-Kutta-Fehlberg method. The effect on the boundary layer flow and heat transfer behaviours of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Suspension of solid nanoparticles like water, oil, and ethylene glycol in the conventional fluids can increase the heat transfer performance. Shape and size are the thermal properties of the solid nanoparticles that highly affect the thermal conductivity of fluid [6][7][8]. An experiment conducted by Choi and Eastman [9] has proved that the incorporation of nanoparticles in the non-Newtonian fluids had greatly boosted the fluid thermal capability.…”
Section: Introductionmentioning
confidence: 99%
“…Suspension of solid nanoparticles like water, oil, and ethylene glycol in the conventional fluids can increase the heat transfer performance. Shape and size are the thermal properties of the solid nanoparticles that highly affect the thermal conductivity of fluid [6][7][8]. An experiment conducted by Choi and Eastman [9] has proved that the incorporation of nanoparticles in the non-Newtonian fluids had greatly boosted the fluid thermal capability.…”
Section: Introductionmentioning
confidence: 99%
“…The nanofluid Buongiorno-Darcy model is employed and concluded that the increase in Brownian motion parameter and thermophoresis parameter has reduced the values of Nusselt number. Next, the flow and heat transfer immersed in a viscoelastic fluid, Jeffrey fluid, and viscoelastic nanofluid have been observed by Widodo et al (2016), Zokri et al (2017;2018) and Mahat et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…The MHD flow of a double stratified micropolar fluid across a vertical shrinking sheet in the presence of suction, heat source effects and chemical reaction was analysed by Khan et al, [23]. Zokri et al, [24] explored the influence of viscous dissipation and suspended nanoparticles on mixed convection flow of Jeffrey fluid from a horizontal circular cylinder. Moreover, a Bingham non-Newtonian fluid flow in Forchheimer porous medium subjected to Hall current was modified by Ewis [25].…”
Section: Introductionmentioning
confidence: 99%